Modelling and control of LCL voltage source converter-based hybrid high voltage alternating current/high voltage direct current system - Saadeh, Mahmood; Hamdan, Mohammad; Saadeh, Osama (Institute of Advanced Engineering and Science, 2025)
Voltage source converters (VSCs) have revolutionized high voltage direct current (HVDC) transmission, offering numerous advantages such as black start capability, absence of commutation failure, and efficient control of bidirectional power flow. This study introduces a comparative analysis of advanced VSC technologies, focusing on a novel series hybrid converter incorporating an inductor-capacitor-inductor (LCL) passive circuit. This configuration is explored for its potential to enhance both high voltage alternating current (HVAC) and high voltage direct current (HVDC) side fault suppression capabilities and improve DC output voltage quality, addressing critical drawbacks of traditional VSCs. Through comprehensive simulations in MATLAB/Simulink, this research evaluates and compares three different converter topologies: the three-level neutral point clamped converter, the hybrid converter with AC side cascaded H-bridge cells, and the LCL hybrid converter. The comparison is based on key performance metrics such as DC output voltage quality, fault suppression capabilities, and system efficiency during normal and fault conditions. The study finds that the LCL hybrid converter outperforms traditional converters by significantly improving DC output voltage quality and enhancing fault suppression capabilities in HVDC systems. It effectively reduces ripple and maintains stability during faults, making it a superior choice for future HVDC converter designs and applications, offering valuable insights for advancing HVDC technology.